Efecto de la concentración del ligante citrato (C6H5O7 3–) en la adherencia de películas de CdS obtenidas por depósito en solución química sobre sustratos de vidrio utilizando el sistema CdCl2–Na3C6H5O7–NaOH–SC(NH2)2: Effect of the citrate ligand (C6H5O7 3–) concentration on the adhesion of CdS films obtained by chemical solution deposition on glass substrates using the CdCl2–Na3C6H5O7–NaOH–SC(NH2)2 system - Rosas-Domínguez, C. J.; Escalante-Bujanda, M. A.; Sandoval-Sánchez, R. I.; Vargas-Durazo, J. T.; Corona-Martínez, D. O.; García-Valenzuela, J. A. (Journal of BioProcess and Chemical Technology (JBCT), 2026)
The synthesis of cadmium sulfide films by chemical solution deposition produces toxic cadmium waste. Thus, it is important to decrease the concentration of cadmium salt used in the reaction. The problem is that a decrease in cadmium ions concentration results in films that do not adhere to the glass substrates that are free of “active” atoms. As a solution, a simple chemical formulation is presented here that employs a low concentration of cadmium ions but still permits adhesion to impurity-free glass substrates. The way to achieve it, and which is demonstrated in this work, is the modulation of the concentration of the rest of the reagents, particularly the ligand concentration (in this case, citrate), whose decrease allows the use of a lower concentration of cadmium salt, resulting in adherent films; the effect of decreasing the citrate concentration is to increase the concentration of available cadmium ions, which promotes the adhesion of the films, without adding more cadmium salt to the reaction solution. In this way, a systematic study of the effect of decreasing the citrate concentration until obtaining formulations that use the minimum ligand concentration that produces sufficiently thick and adherent cadmium sulfide films is presented below. To understand adhesion, the three factors that determine adhesion are explained in the introduction: substrate reactivity (surface sensitization), cadmium ions concentration, and temperature.
Keywords: Adhesion; Thin films; Cadmium sulfide; Chemical solution deposition; Sodium citrate